Strategic Prospect applied to the public finance: An exercise for the management of its assets and liabilities to year 2030 - Jiménez Sotelo, Renzo A. (2018)
This paper shows a methodological application of prospective strategic planning as a tool to improve future decision making within the state. To do this, the method of scenarios and pro-spective strategy applied to an exercise of improving the management of the financial equity of the public treasury of a small, open and partly dollarized economy such as the Peruvian one is used. In the exercise, five possible future scenarios were designed from which an as-pirational scenario was constructed, based on current results and lessons from the past, in order to respond to what could happen (risks and opportunities) and the strategic actions that should be implemented to achieve the objectives of such scenario. The document recognizes the different historical importance given to the prospective as a tool of strategic anticipation within the states of developed countries, which unfortunately has not been given in most Lat-in American countries. Therefore, it is hoped that document will contribute to spread the via-bility of its application in government entities of these countries.